Conditions for the existence and asymptotic of a class of solutions of essential nonlinear differential equations of the second order (in Russian) - А. A. Kozma (Математичні Студії, 2011)
We consider the ordinary differential equation of the second order containing in the righthand side the sum of nonlinearities correctly varying concerning unknown function and its derivative of the first order. Necessary and sufficient conditions of existence of a wide class of monotone solutions, and exact asymptotic representations of solutions from the given class in a neighborhood of a singular point are established.